The Relationship between Anxiety Level and Learning Achievement in Math Subject in Primary School Students - Rizqi Meiliyani (Scientia Psychiatrica, 2021)
Introduction. This study aims to determine whether there is a relationship between anxiety and mathematics learning achievement in the material of volume building space in primary school students in Bantul, Yogyakarta. Methods. This research uses quantitative research with a survey method through a correlation approach. The population in this study were students in fifth-grade of primary school in Jetis Bantul. The total participant in this study was 28 students. Measuring instruments in this study are math problems, interviews and anxiety scales. The analysis technique used in this study is with the help of the SPSS 22.0 For Windows program. Results. The normality test calculation results show a significance on the anxiety scale of 0.200, while the mathematics learning achievement is 0.010. Based on the hypothesis test calculation using the Spearman correlation, the correlation between anxiety and mathematics learning achievement is that there is a relationship between anxiety and achievement learning math but not significant. Conclusion. There is a relationship between anxiety and achievement in mathematics in a fifth-grade primary school student.